Introduction and optimization of the in-vitro method for determining the hemocompatibility of modified poly(ethylene)terephthalate surfaces: Vpeljava in optimizacija in-vitro metode za določanje hemokompatibilnosti modificiranih polietilenteraftalatnih površin - Stana, Jan; Stropnik, Domen; Strnad, Simona; Indest, Tea; Jevšek, Marko; Košir, Gorazd (Acta Medico-Biotechnica, 2022)
Purpose: Internationally-accepted standards have been developed for a range of tests and parameters for characterising the in-vitro interactions of biomaterials with blood. However, there are, as yet, no standards concerning the size, design and type of such in-vitro testing systems (1). Since the development of hemocompatible biomaterials provides a very important challenge in material science, there is a need for further progress in finding reliable and standardized methods for hemocompatibility testing (2). The aim of this research was to introduce a method for analyzing the hemocompatibility of different chemically-modified surfaces. Polyethylene terephthalate (PET), with surface modifications using differentpolysaccharides and their derivatives, were chosen because of their promising biocompatible properties and numerous potential biomedical applications.Methods: A modified hemoglobin-free method was used to determine the antithrombogenicity of the modified PET surfaces (4). The method was optimized for shaking rate, the addition of buffer, and blood temperature to decrease measuring errors. Five differently-modified PET surfaces were analyzed: chemically pre-treated PET and PET treated with chitosan, fucoidan, sulphated chitosan and heparin. Glass was used as a standard thrombogenic surface.Results: The results showed that a lower shaking rate, the addition of buffer, and blood cooling prior to measurement significantly decreased the standard deviation of the measurement results by a total of about 89 %.Conclusions: We believe this optimized hemoglobinfree method is suitable for distinguishing between chemically and structurally-different surfaces, such as glass and PET. The differences between PET surfaces coated with different polysaccharides were, however, less pronounced.
Keywords: biomaterials; poly(ethyleneterephthalate); hemocompatibility; surface modification; in-vitro method